Membaca Semangat Hermeneutika Hanafi - Mahatma, Masmuni (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2015)
Alquran cannot be detached from the chain of history accompanying it. Alquran has always been associated with sacred values it contains. That is it’s fitrah. Hasan Hanafi, born in Cairo, develops a unique hermeneutics to view Alquran as revelation. In safeguarding the originality of the Scripture as much as possible, the potential of reason and thought cannot be avoided as well. For the Scripture is an ideal ‘mirror’ of the expressions of the reality in life together with all the social dynamic continuously approaching the believers. Without the involvement of reason and thought the Scripture might not be so much different from an ‘inscription’, which is passive, cold, and barely engendering things characterised as dialogical and productive. Viewed in its process of descent to human beings, the scriptural revelation is not something suddenly flying and drifting without reason. The revelation is closely related with the reality (of the past) tied up together by Allah. Each verse or set of verses in the Scripture has mirrored solution to particular problem in the banality of individual and communal life. The Scripture is not simply a ‘text’, for it is always breathing ‘context’. By having context, the Scripture cannot be uncoupled from the social reality of the believers who put their trust in it. The Scripture is a text merging with context, which in turn illuminates the believers all around the world.